SEVEN KNOWN SPECIES OF NYGOLAIMODEA AND MALE RECORD OF CLAVICAUDA SYMMETRICUS (WILLIAMS, 1958) AHMAD AND JAIRAJPURI, 1982 - ANANDI, Y.; MOHILAL, N.; DHANACHAND, CR. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
Seven known species of the superfamily Nygolaimoidea, Aquatides aquaticus (Thorne, 1930) Thome, 1974, Aquatides thornei (Schneider, 1937) Thome, 1974, Solididens vulgaris (Thome, 1930) Thome, 1974; Laevides imphalus Ahmad & Jairajpuri, 1980; Laevides laevis (Thome, 1939) Thome, 1974; Nygellus clavatus Thorne, 1939 and Clavicauda symmetricus (Williams, 1958) Ahmad & Jairajpuri, 1982 from Manipur are presented. Male of Clavicauda symmetricus is reported for the first time. The male has L = 1.56-1.61mm, a = 63-65, c = 14-15, tail= 107-110µm, spicules = 24-27µm.